The Influence of Internal Control and Management Control System (MCS) on Employee Performance with Work Commitment as a Moderation Variable - Noor, Vera Fitriani; Ismail, Tubagus; Yulianto, Agus Solikhan (Eduvest - Journal of Universal Studies, 2023)
This study aims to analyze the effect of Internal Control and Management Control System (MCS) on Employee Performance with Work Commitment as a moderating variable (Empirical Study on Pandeglang Regency Government). The research methodology used is a quantitative method, using primary data obtained from the results of distributing questionnaires to respondents. The data analysis technique used is multiple linear regression analysis with PLS software. The results of this study indicate that Internal Control influences Employee Performance, Management Control System (MCS) influences Employee Performance, Work Commitment moderates Internal Control influences Employee Performance, and Work Commitment moderates Management Control System (MCS) influences Employee Performance.